Characterizing Oligomeric Hydroxyl Silicon Oils by MALDI-TOF MS With the Pyridine-Modified Matrix - Xiaoxiao Zhang (Frontiers Media S.A., 2021)
Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) is a powerful technique for analysis of various polymers, but it is still very difficult to characterize silicone oil due to its poor ionization efficiency. In this work, oligomeric hydroxyl silicone oils were successfully characterized by MALDI-TOF, by using pyridine-modified 2,5-dihydroxylbenzoic acid (DHB) as the matrix. Furthermore, the mixed crystal of DHB and hydroxyl silicone oil was analyzed by scanning electron microscopy (SEM) and energy disperse spectroscopy (EDS), and the analytical results verified that modification with pyridine could remarkably improve the solubility of hydroxyl silicone oil in DHB, leading to the enhancement of its ionization efficiency in MALDI. The analysis of the MS spectra of a series of hydroxyl silicone oils indicated that they tended to be ionized by the attachment with Na+, and the average molecular weight and the degree of polymerization were measured for several oligomeric hydroxyl silicon oils.